PEMANFAATAN KOMBUCHA BUNGA TELANG (Clitoria ternatea L) SEBAGAI UPAYA DALAM MENCEGAH STUNTING DAN MENINGKATKAN IMUNITAS DI DESA NGAGLIK MAGETAN PARANG - Firman Rezaldi; Irmawati Mathar; Rina Nurmaulawati; Achmad Vindo Galaresa; Priyoto Priyoto (Jurnal Abdimas Bina Bangsa, 2023)
One of the trending topics that is currently happening in Indonesia is stunting. This disease is caused by the failure rate of growth and development in children where children who are stunted ideally are chronically malnourished. This requires special attention from the local government and the state so that cases of stunting that occur in children do not tend to experience an increase. One of the efforts to prevent stunting is the need for education from the surrounding environment, so this has led to the desire of the team of lecturers from Stikes Bhakti Husada Mulia Madiun to provide education about the benefits of butterfly pea flower kombucha and the process of making butterfly pea flower kombucha to improve immune system and also increase insight into the people who live in Ngaglik Village. Pararang District. Magetan Regency. East Java. The first step in carrying out community service includes obtaining permits for the local community, conducting initial identification regarding stunting problems, determining activity targets and objectives, conducting outreach and education consisting of a pre test. Evaluate and achieve program achievements through check list evaluations. The results of the evaluation have proven that the people in Ngaglik Village have increasing insight regarding the systematic utilization and production of telang flower kombucha which can be applied as a probiotic drink to enhance the immune system, therapeutic, nutritious drink, nutritious animal feed nutrition, and application of liquid fertilizer eco-friendly organic